Assessment and comparison of the effects of two techniques on hamstring flexibility - Navega, Marcelo Tavella [UNESP]; Paleari, Bruna; Morcelli, Mary Hellen (Pontifícia Universidade Católica do Paraná, 2014)
Introduction There are several stretching techniques that help increase flexibility, however, there are still questions regarding which method leads to the most effective gains. Objectives To assess and compare the effects of two stretching techniques, namely proprioceptive neuromuscular facilitation (PNF) and static stretching on the flexibility of hamstring muscles of young women. Methods The study sample consisted of 45 young women, mean age 20.45 (± 1.66),assigned to one of three groups: static stretching group (SSG, n = 15), proprioceptive neuromuscular facilitation group (PNFG, n = 15) and control group (CG, n = 15). Both SSG and PNFG carried out three weekly stretching sessions over a four-week period. The sit and reach and popliteal angle tests were used at the beginning and end of the intervention. Normally distributed data were analyzed using Student’s t-test, whereas data with non-normal distribution were analyzed using the Wilcoxon test, to compare initial and end measurements for each technique. Finally, we used the Mann-Whitney U test to compare both techniques with each other. A significance level of 5% (p < 0.05) was adopted. Results There was a significant increase in hamstring flexibility when analyzing the assessments and reassessments of both stretching protocols. Conclusions Both techniques were effective in increasing hamstring flexibility and there were no significant differences to indicate which one is better in increasing the flexibility of this muscle group.

Introdução Existem diversas técnicas de alongamento que auxiliam o aumento de flexibilidade, entretanto ainda prevalecem dúvidas sobre qual método aponte ganhos majoritariamente eficazes. Objetivos Avaliar e comparar os efeitos das técnicas de alongamento Facilitação Neuromuscular Proprioceptiva (FNP) e o Alongamento Estático na flexibilidade dos músculos isquiotibiais de jovens mulheres. Métodos Participaram do estudo 45 jovens, mulheres, com média de idade entre 20,45 (± 1,66), que foram divididas em três grupos: grupo alongamento estático (GAE, n = 15), grupo alongamento facilitação neuromuscular proprioceptiva (GFNP, n = 15) e grupo controle (GC, n = 15). Os grupos GAE e GNFP realizaram três sessões semanais de alongamento durante quatro semanas. As voluntárias foram avaliadas por meio do Teste Sentar e alcançar e pelo Teste do Ângulo poplíteo no início e ao fim das intervenções. Os dados com distribuição normal foram analisados pelo Teste t de student, para os dados com distribuição não normal, foi utilizado o Teste de Wilcoxon para comparar cada técnica e o Teste de Mann-whitney para comprar as duas técnicas. Foi adotado o nível de significância de 5% (p < 0,05). Resultados Houve aumento significativo da flexibilidade dos músculos isquiotibiais quando analisadas as avaliações e reavaliações em ambos os protocolos de alongamento. Conclusões Ambas as técnicas são eficazes para o ganho de flexibilidade dos músculos isquiotibiais, não apresentando diferenças significativas que evidenciasse qual delas é a melhor para o ganho de flexibilidade desse grupo muscular.
Avaliação e comparação dos efeitos de duas técnicas de alongamento na flexibilidade dos músculos isquiotibiais
Keywords: Alongamento; Isquiotibiais; Flexibilidade; Mulheres; Fisioterapia; Stretching; Hamstrings; Flexibility; Women; Physical Therapy